2016
DOI: 10.2217/pme-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Bace1 Levels Are Increased in Plasma Of Alzheimer’S Disease Patients Compared with Matched Cognitively Healthy Controls

Abstract: Blood-based diagnostic tools are desired to improve AD diagnosis. BACE1 plasma levels could provide an additional diagnostic tool for AD in association with neuropsychological tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This biochemical characterization may serve for a better evaluation of BACE1/β-secretase activity as a potential biomarker for AD. BACE1 has been considered as a promising candidate biomarker due to its role in the generation of Aβ and the demonstration that the β-secretase activity can be assayed in CSF and plasma (Gonzales et al, 2011;Holsinger et al, 2004;Manzine et al, 2016;Shen et al, 2018;Wu et al, 2008;Wu et al, 2012;Zetterberg et al, 2008). However, to date, little is known about the cell biology and biochemistry of BACE1 in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…This biochemical characterization may serve for a better evaluation of BACE1/β-secretase activity as a potential biomarker for AD. BACE1 has been considered as a promising candidate biomarker due to its role in the generation of Aβ and the demonstration that the β-secretase activity can be assayed in CSF and plasma (Gonzales et al, 2011;Holsinger et al, 2004;Manzine et al, 2016;Shen et al, 2018;Wu et al, 2008;Wu et al, 2012;Zetterberg et al, 2008). However, to date, little is known about the cell biology and biochemistry of BACE1 in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA BACE1 level was dramatically up-regulated in AD patient’s plasma compared with normal control subjects, while no significantly alteration of plasma lncRNA 17A, 51A and BC200. Accordantly, Manzine et al also confirmed that plasma BACE1 level was elevated in AD patients [86]. However, Marison et al proved that there was no dramatically difference of BACE1 expression in blood between control, AD and non-AD neuropathology’s individuals.…”
Section: Circulating Lncrnas and Alzheimer’s Diseasementioning
confidence: 92%
“…Some studies employed assays based on polyclonal antibodies [34,68], which do not support the reproducibility of the assays on the longer term (cfr. long-term supply of antibodies with steady characteristics, lot-tolot consistency of the assay, etc.).…”
Section: Methodological and Technological Challengesmentioning
confidence: 99%
“…Both BACE1 activity and protein concentrations in blood (mostly plasma but in some cases serum) are significantly increased in MCI individuals or patients with ADD compared to HC individuals, with a trend across different disease stages reflecting the direction of expression of the reported CSF biomarkers [34][35][36].…”
Section: Bace1 Biomarkers In Plasmamentioning
confidence: 99%